An Open-Labeled, Multicentric, Clinical Trial to Substantiate the Safety and Efficacy for the Combination of Salbutamol, Etofylline and Bromhexine in the Treatment of COPD - Kiran, Mayuresh; Pawaskar, Lalit (International Journal of Innovative Research in Medical Science, 2018)
Background: As per WHO, COPD is a lung disease characterized by chronic obstruction of lung airflow that interferes with normal breathing and is not fully reversible. COPD can be treated by the combination of bronchodilators of different mechanisms and duration of action and mucolytic agents. So for the treatment of COPD we have selected the combination of Bromhexine, Salbutamol, and Etophylline. Different dose combination of these drugs were used for children of age 2 to 12 years and adults of age 18 to 65 years. For children the combination of Bromhexine 4mg, Salbutamol 1mg and Etophylline 50mg per 5ml syrup was used and for adults the combination of Salbutamol 2mg, Etofylline 200mg and Bromhexine 8mg per tablet was used. Methodology: Out of total 302 patients, 267 completed the study. Efficacy assessment was made by analysing the reduction in Cough Severity Score (CSS) extrapolated to four point Likert-type scale and FEV1. Safety assessment was made by analysing the adverse events experienced by the patients. Results: At baseline, mean CSS was found to be 6.03 which reduced to 3.46 (day 3) and further reduced to 1.52 (day 5). One point reduction in Likert-type symptom scale from Moderate to Mild took in just 5 days. At day 1, %FEV1 was 57.61% increased to 70.49% at day 3 and 81.17% at day 5. Overall 45 episodes of adverse events occurred and were of mild intensity. Conclusion: A combination of Bromhexine, Salbutamol and Etophylline is safe and effective for the treatment of COPD.